Institutional Change and the Impact Towards Innovation Competitiveness in the Industrial Development of The Batam Free Trade Zone - B. A. Wiryawan (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2019)
The purpose of this study is to evaluate an implementation of the batam free trade zone in industrial development. A survey was conducted in 2015 involving 17 firms from different areas of the zone. Relationships between variables were established using Fischer’s Exact Test. Result indicates that there is significant relationship between institutions and innovation, judging by research, designing, and development related activities, fewer than 95% confidence level. The problem lies in the conflicts between the FTZ Authority and the local governments, as the latter continued to dominate the institutional settings. The results indicated that weak vision towards FTZ policy and zero-sum approach by key actors contributed the most to the failure in reindustrialize the zone.